REVIEW OF RESEARCH ON BEAM STRUCTURES WITH HYBRID REINFORCEMENT - Yurochko , Н. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2025)
This article presents an extended analysis of recent research on beam structures with hybrid reinforcement that combines different types of reinforcement materials such as steel bars, composite rods (GFRP, BFRP, CFRP), fiber, and prestressed elements. The review includes both experimental and numerical studies that investigate the effects of various reinforcement combinations on the fundamental characteristics of beams: load-bearing capacity, crack resistance, ductility, and overall performance. Several examples of hybrid reinforcement applications are provided, including combinations with advanced types of concrete such as ultra-high-performance concrete (UHPFRC), geopolymer concrete, and fiber-reinforced concrete. Particular attention is given to research where the combination of GFRP with steel and fiber provided an optimal balance of stiffness, corrosion resistance, and cost-effectiveness. It has been found that the addition of fiber – especially steel, polymer, or natural fibers (jute, polypropylene) – has a positive influence on the post-cracking behavior of beams. The article also analyzes structural features of anchorage systems used in hybrid reinforcement schemes. It is shown that the use of prestressed composite reinforcement in combination with traditional steel reinforcement allows a reduction in structural weight while maintaining strength characteristics. Based on the comparative analysis of numerous studies, the article identifies effective hybrid reinforcement schemes that may be recommended for practical implementation in infrastructure construction, including the production of beams for bridges, floors, and other critical structural elements. The need for further development of regulatory frameworks for the adoption of such reinforcement systems in engineering practice is emphasized, as well as the importance of further investigation into the influence of geometric, technological, and material parameters on the behavior of hybrid reinforced elements.